Chemical Analysis of Wet Deposition Sequential Samples at Istanbul, Turkey - (:unkn) unknown (My University, 2018)
In this study, the relations between wet deposition fluxes of major ions, concentrations and rain intensity in the precipitation events occurring on a) November 10th, 2007 and b) December 05th, 2007 are presented. The variations on the ion concentrations were investigated during the rain events. The concentrations of all ions drastically decreased to minimum levels in the first sub sequential events for each the rain events. Some ions had a significant decrease in concentrations in comparison with other ions, because they have higher concentration in the atmosphere as much as they exist in the large atmospheric particles which are being sourced from in the soil or sea. The strongest relation between the wet deposition flux and the rain intensity were found for Ca2+ and SO42- among the all the ions sampled on November 10th, 2007. It was found that K+ and NO3- concentrations sampled on December 05th, 2007 had a positive correlation with rain intensity; on the other hand, other ions had a negative correlation. Positive correlations were found between wet deposition flux and the rain intensity for all ions in each rain events.